AlFeO3@SiO2@SO3H as a magnetic nanocatalyst for the synthesis of mono/bis-dihydropyrimidin-2-ones and dihydropyridines as pharmaceutically active compounds - Bodaghifard, Mohammad Ali; Ahadi, Najmieh; Ebrahimi, Faranak; Hamidinasab, Mahdia (Journal of Composites and Compounds, 2023)
In this research, the preparation of a reusable AlFeO3@SiO2@SO3H nanostructure as a perovskite-based magnetic nanomaterial is described. The structure of prepared AlFeO3@SiO2@SO3H was characterized by FT-IR, XRD, FE-SEM, EDS, TGA, and VSM analyses. The prepared acidic hybrid nanocatalyst showed high thermal stability and used as an efficient magnetic nanocatalyst in the synthesis of 3,4-dihydropyrimidin-2-one, and mono/bis 1,4-dihydropyridine derivatives as pharmaceutically active heterocycles under solvent free conditions. High efficiency of procedure, good yields, short reaction times, magnetic recovery and reusability of nanocatalyst, high thermal stability of catalyst, and environmentally benign conditions are highlights of this new protocol.